In Situ Study the Dynamics of Blade‐Coated All‐Polymer Bulk Heterojunction Formation and Impact on Photovoltaic Performance of Solar Cells. Issue 6 (26th January 2023) - Yao, Nannan; Fan, Qunping; Genene, Zewdneh; Liu, Heng; Xia, Yuxin; Wen, Guanzhao; Yuan, Yusheng; Moons, Ellen; van Stam, Jan; Zhang, Wei; Lu, Xinhui; Wang, Ergang; et al.
Abstract : All‐polymer solar cells (all‐PSCs) have achieved impressive progress by employing acceptors polymerized from well performing small‐molecule non‐fullerene acceptors. Herein, the device performance and morphology evolution in blade‐coated all‐PSCs based on PBDBT:PF5–Y5 blends prepared from two different solvents, chlorobenzene (CB), and ortho‐ xylene ( o‐ XY) are studied. The absorption spectra in CB solution indicate more ordered conformation for PF5–Y5. The drying process of PBDBT:PF5–Y5 blends is monitored by in situ multifunctional spectroscopy and the final film morphology is characterized with ex situ techniques. Finer‐mixed donor/acceptor nanostructures are obtained in CB‐cast film than that in o‐ XY‐cast ones, corresponding to more efficient charge generation in the solar cells. More importantly, the conformation of polymers in solution determines the overall film morphology and the device performance. The relatively more ordered structure in CB‐cast films is beneficial for charge transport and reduced non‐radiative energy loss. Therefore, to achieve high‐performance all‐PSCs with small energy loss, it is crucial to gain favorable aggregation in the initial stage in solution. Abstract : In situ and ex situ investigations on blade‐coated all‐polymer bulk‐heterojunctions give a deeper understanding of the morphology formation process, which demonstrates that polymer chain conformation in solution will persist in solid. The better photovoltaic performance with reduced non‐radiative energy loss is the result of the relatively ordered structure. This work provides insights into the correlation between morphology formation and device performance.